Teaching and Learning Science as a Tool for Human Sustenance: The Non-Science Community’s Expectations for School Science - Kenneth Adu-Gyamfi; Isaiah Atewini Asaki; Abigail Fiona Dzidzinyo; Charles Deodat Otami (Education Sciences)
The world, through the UN and its agencies, is looking for ways to sustain the environment that we live in via the SDGs. The importance of school science in achieving the SDGs cannot be overstressed. The literature abounds on the need for school science to relate to the interests and expectations of students and the importance of teachers and scientists of school science in finding solutions to sustaining our world. However, little is known about the interests and expectations of other members of our society. Consequently, we studied the expectations of members of the non-science community whose children are learning science in schools and colleges. Using a phenomenological approach, we employed interview schedules to study 15 participants, comprising 5 women and 10 men, on what they thought about science and scientists and their expectations regarding learning science in school in the 21st century, saddled with global pandemics, global warming, flooding, and other natural disasters. The thinking and expectations of the participants were analysed using a thematic analysis with constant comparison procedures to arrive at five views and expectations of school science by the non-science community. Although the participants were grateful to the science community for rising to the challenge of COVID-19, they expected school science teachers to use innovative approaches to prepare their students for future challenges, as the world lost many human lives to the COVID-19 pandemic. These findings will inform science curriculum planners about the content and pedagogies to recommend for schools and colleges.